Petrographic records of two metamorphic events in the Lesser Himalayan metabasites, Modi Khola section, central Nepal - Paudel, Lalu (Bulletin of the Department of Geology, 2008)
Metabasites of the Lesser Himalaya along the Modi Khola valley in central Nepal are the supracrustal dikes and sills of basic igneous rocks emplaced in the clastic sediments and later metamorphosed together with the host rocks. They contain almost a constant metamorphic mineral assemblage of Ca-amphiboles+plagioclase+biotite+quartz±epidote±chlorite+(Fe-Ti oxides). Amphiboles occur in the form of porphyroblast and recrystallized matrix. The porphyroblasts are zoned with actinolitic cores and hornblende rims. The recrystallized matrix ranges in composition from actinolite in chlorite zone to hornblende in biotite and garnet zones. The cores of porphyroblasts are pre-kinematic and were probably formed prior to the Tertiary Himalayan orogeny. The rims of porphyroblasts and matrix amphiboles are syn-kynematic and were formed during the Upper Main Central Thrust activity in the Tertiary. The systematic changes in amphibole compositions as well as textural characteristics of metabasites are in good agreement with the classical concept of increasing metamorphic grade and intensity of deformation structurally upwards towards the Upper Main Central Thrust in the Lesser Himalaya.           doi: 10.3126/bdg.v11i0.1428 Bulletin of the Department of Geology, Tribhuvan University, Kathmandu, Nepal, Vol. 11, 2008, pp. 5-12